SPE International Symposium on Oilfield Chemistry 2009
DOI: 10.2118/121550-ms
|View full text |Cite
|
Sign up to set email alerts
|

Formate Brines for HPHT Well Control—New Insights into the Role and Importance of the Carbonate/Bicarbonate Additive Package

Abstract: This paper describes new research into the role and importance of the carbonate/bicarbonate pH-buffer added to formate based well construction fluids along with a newly developed field method for determining buffer concentrations. For many years it has been recommended practice to buffer formate brines with carbonate and bicarbonate for corrosion control. Bicarbonate is also the product of the dominant thermal decomposition reaction in formate brine. Since this is an equilibrium reaction, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…With such fluid, as a rule, lower rheology, ECD and pressure losses in the well will be provided in contrast to traditionally used oil-based mud. It contributes to increasing drilling efficiency, especially in conditions of the narrow mud window [14,15,41]. It is also worth noting that the analysis of scientific literature proves that formate drilling systems are compatible with formation fluids, which creates conditions for increasing MPR and decreasing the contamination of bottomhole.…”
Section: Aims and Tasks Of The Researchmentioning
confidence: 98%
“…With such fluid, as a rule, lower rheology, ECD and pressure losses in the well will be provided in contrast to traditionally used oil-based mud. It contributes to increasing drilling efficiency, especially in conditions of the narrow mud window [14,15,41]. It is also worth noting that the analysis of scientific literature proves that formate drilling systems are compatible with formation fluids, which creates conditions for increasing MPR and decreasing the contamination of bottomhole.…”
Section: Aims and Tasks Of The Researchmentioning
confidence: 98%
“…It should be noted that pH measurements in concentrated brines do not refl ect the actual concentration of H + in the solution, as the pH electrodes will be affected at high salt concentrations (Howard 2009). The pH and the density were measured on site and the results are plotted in Figs.…”
Section: Analysis Of Aqueous Phase Separated From the Samplesmentioning
confidence: 99%
“…Recently, materials such as super 13%Cr martensite stainless steel (S13Cr) has been considered as a tubing and casing material for such hash conditions based on its good corrosion resistance, low cost, and excellent mechanical properties. Along with the growing understanding of the influence of aggressive substances on the corrosive of formate brines (Bungert et al, 2000;Howard et al, 2009), further study of the corrosion behavior of S13Cr immersed in the formate brines as well as the evolution of the corrosion scales on the surface is urgently pressed. It has been reported that both Fe and Cr elements in the matrix significantly contributed to the corrosion-resistant stainless steel (SS) in an acidized KCOOH solution by comparing the polarization curves between pure metal and 304 SS; Ni promotes the stability of the passive film on the surface as well as the mechanical property (Sekine and Chinda, 1984).…”
Section: Introductionmentioning
confidence: 99%